Modified chitosan scaffolds: Proliferative, cytotoxic, apoptotic, and necrotic effects on Saos-2 cells and antimicrobial effect on Escherichia coli. (May 2016) - Ucar, Seniz; Ermis, Menekse; Hasirci, Nesrin
Scaffolds used in tissue engineering applications should have high biocompatibility with minimum allergic, toxic, apoptotic, or necrotic effects on the growing cells and newly forming tissue and, if possible, have antimicrobial property to prevent infection at the host site. In this study, novel micro-fibrous chitosan scaffolds, having mineralized bioactive surface to enhance cell adhesion and a model antibiotic (gentamicin) to prevent bacterial attack, were prepared. The effects of the scaffolds on proliferation, viability, apoptosis, and necrosis of Saos-2 cells are reported for the first time. Wet spinning technique was used in the scaffold preparation and biomineralization was achieved by incubating them in five-time concentrated simulated body fluid for 2, 7, or 14 days (coded as CH-BM/2, CH-BM/7, and CH-BM/14, respectively). Gentamicin, an effectively used antibiotic in bone treatments, was loaded by vacuum-pressure cycle. Energy-dispersive X-ray results demonstrated that Ca/P ratio of the mineral phase varies depending on the incubation period. When the scaffolds were cultured with Saos-2 cells, cell adhesion and extracellular matrix formation occurred on all types of scaffolds. Alamar Blue cytotoxicity tests showed correlation among mineral concentration and cytotoxicity where CH-BM/2 had significantly more favorable properties. For all types of scaffolds, apoptosis and necrosis were less than 10%, meaning the samples are biocompatible. Gentamicin-loaded scaffolds showed high antimicrobial efficacy against Escherichia coli . The presence of mineral phase enhanced the adhesive capacity of cells and entrapment efficiency of antibiotic. These results suggest that the bioactive and antimicrobial scaffolds prepared in this study can act as promising matrices in bone tissue engineering applications.